Impact of Sleep Apnea on Cardioembolic Risk in Patients With Atrial Fibrillation: Data From the ESADA Cohort - Pengo Martino F; Faini Andrea; Grote Ludger; Ludka Ondrej; Joppa Pavol; Pataka Athanasia; Dogas Zoran; Mihaicuta Stefan; Hein Holger; Anttalainen Ulla; Ryan Silke; Lombardi Carolina; et al. (American Heart Association, 2022)
Background and purpose: An accurate determination of the cardioembolic risk in patients with atrial fibrillation (AF) is crucial to prevent consequences like stroke. Obstructive sleep apnea (OSA) is a known risk factor for both AF and stroke. We aim to explore a possible association between OSA and an increased cardioembolic risk in patients with AF.
Methods: We assessed data from the ESADA (European Sleep Apnea Database) cohort where patients with known AF and OSA were included. Parameters of OSA severity and related hypoxia like lowest Spo2 and 4% oxygen desaturation index were analyzed. Patients were stratified according to their cardioembolic risk estimated with the CHA2DS2-VASc score.
Results: From the initial cohort of 14 646 patients, a final set of 363 patients were included in the analysis. Indices of hypoxia during sleep were associated with increased CHA2DS2-VASc score (4% oxygen desaturation index 17.9 versus 29.6 versus 30.5 events/hour and the lowest Spo2 81.2 versus 77.8 versus 77.5% for low, moderate, and high cardioembolic risk, respectively, P<0.05).
Conclusions: These results support the potential role of OSA-related hypoxia in the risk for cardioembolic complications such as stroke in patients with AF.